Impact of Anabolic Androgenic Steroids on Cardiovascular and Mental Health: Current Literature Review - Kardaszewski, Piotr; Kapturska, Natalia; Cymerys, Kinga; Mąka, Magdalena; Kadłubek, Sabina; Kalinowski, Szymon; Woźniak, Julia; Kamiński, Jakub; Sikora, Dominik; Góralczyk, Ewa (Quality in Sport, 2026)
Introduction and purpose: Anabolic Androgenic Steroids were introduced in bodybuilding and treatment of medical conditions due to anabolic effect. Nowadays their popularity is rising, so is accessibility and range of substances present. Evidence shows severe impact AAS abuse has on overall health, especially on cardiovascular and mental domains. The aim of this review is to consolidate knowledge about AAS adverse effects. Materials and methods: Medical databases such as PubMed, Google Scholar and PMC were searched, data analyzed and put into the single article. State of knowledge: AAS use becomes a rising issue these days with millions engaged in various sports, taking supraphysiological doses. AAS abuse is taking its toll having a negative impact on cardiovascular health increasing probability of diseases or death. Moreover AAS-induced psychiatric morbidity is also observable causing serious impairment of everyday functioning. Although evidence is solid and well documented there are still many understudied areas that require further research. Conclusions: AAS use is an independent, major and historically underrecognized risk factor for both cardiovascular disease and psychiatric morbidity. Due to persisting underrepresentation of a matter future research priorities should include large prospective inception cohorts with co-primary cardiac and psychiatric endpoints, compound-specific risk profiling adolescent exposure studies and adequately powered treatment trials.